The Lived Experience of Anxiety Disorder Patients: Narrative Inquiry - Bamijoko-Okungbaye, Abiola (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2020)
Background: Anxiety disorder patients tend to feel that they are misunderstood and judged. Their lived experiences were understudied in clinical setting where the focus is mostly on their response to treatment. Apart from the stigma associated with the disorder, they face negative social perceptions, which affect their ability to interact with their community, disrupting their healing path. A narrative account in mental health can lead to the creation of a healthier society. This research examines how people with anxiety disorders view themselves and ascribe meaning to the stigma surrounding their condition. Method: A narrative analysis of case studies in Europe, each patient sharing their in-depth lived experiences with anxiety disorders. Results: Nadir's experience was initially expressed and as the participants gained a moderate, balanced level of self-awareness through narrative approaches, they quickly develop coping strategies that are essential to their recovery. Conclusion: Narrative mental health might be an area that needs refocusing during the treatment of anxiety disorders patients.